Pengaruh Perilaku Sikap Kerja terhadap Kinerja Pelayanan Karyawan di Asstro Highlands Ciater - Qurrota Ayun; Rusman Frendika; Firman Shakti Firdaus (Bandung Conference Series: Business and Management, 2023)
Abstract. Astro highlands ciater As a place to relax with family, colleagues or relatives, vacation activities, family time and business activities. offers culinary delights amidst the coolness of the tea gardens. Asstro Highlands Ciater in the form of work attitude behavior in the ability to socially relate to fellow employees has not gone well, there is a lack of respect for one another. Based on this phenomenon, the problems in this study are formulated as follows: (1) How is the work attitude of the employees at Astro Highlands Ciater? (2) How is the service performance of the employees at Astro Highlands Ciater? (3) How much influence does work attitude behavior have on employee service performance at Astro Highland Ciater?. This research uses descriptive and verification analysis methods and operates the calculations using the IBM SPSS Version 25.0 program. Respondents in this study were Asstro Highlands Ciater employees, totaling 73 people. The variables studied in this study are work attitude behavior (X) and employee service performance (Y). Data collection was carried out by field research (Field Research) and library research (Library Research). The results of this study conclude that: (1) Asstro Highlands Ciater Employee Service Attitude Behavior is included in the "Good" category, (2) Asstro Highlands Ciater Employee Service Performance is included in the "Very Good" category, (3) Based on the results of the study there is an influence positive and significant relationship between work attitude behavior and employee service performance has a low effect. Keywords: Work Attitude Behavior, Employee Service Performance, Asstro Highlands Ciater Abstrak. Asstro highlands ciater Sebagai tempat bersantai dengan keluarga, rekan kerja, atau kerabat, kegiatan liburan, family time maupun kegiatan berbisnis. menawarkan sajian kuliner di tengah sejuknya kebunteh. Asstro Higlands Ciater berupa tingkah laku sikap kerja dalam kemampuan berhubungan sosial dengan sesama karyawan belum berjalan dengan baik, terdapat rasa kurang menghormati satu sama lain. Berdasarkan fenomena tersebut, maka permasalahan dalam penelitian ini dirumuskan sebagai berikut: (1) Bagaimana perilaku sikap kerja karyawan pada Asstro Highlands Ciater? (2) Bagaimana kinerja pelayanan karyawan pada Asstro Highlands Ciater? (3) Seberapa besar pengaruh perilaku sikap kerja terhadap kinerja pelayanan karyawan pada Asstro Highland Ciater ?. Peneleitian ini menggunakan metode analisis deskriptif dan verifikatif dan mengoprasikan perhitungannya menggunakan program IBM SPSS Versi 25,0. Responden pada penelitian ini yaitu Karyawan Asstro Highlands Ciater, yang berjumlah 73 orang. Variabel yang dikaji pada penelitian ini yaitu Perilaku Sikap Kerja (X) dan Kinerja Pelayanan Karyawan (Y). Pengumpulan data dilakukan dengan penelitian lapang (Field Research) dan studi kepustakaan (Library Research). Hasil penelitian ini menyimpulkan bahwa : (1) Perilaku Sikap Kerja Pelayanan karyawan Asstro Highlands Ciater termasuk ke dalam kategori “Baik”, (2) Kinerja Pelayanan Karyawan Asstro Highlands Ciater termasuk pada kategori “Sangat Baik”, (3) Berdasarkan hasil penelitian terdapat pengaruh positif dan signifikan antara Perilaku Sikap Kerja terhadap Kinerja Pelayanan Karyawan berpengaruh rendah. Kata Kunci : Perilaku Sikap Kerja, Kinerja Pelayanan Karyawan, Asstro Highlands Ciater